"I am busy surviving" - Views about physical exercise in older adults scheduled for colorectal cancer surgery. Issue 3 (April 2020) - Agasi-Idenburg, Carla S.; Zuilen, Mieke Koning-van; Westerman, Marjan J.; Punt, Cornelis J.A.; Aaronson, Neil K.; Stuiver, Martijn M.
Abstract: Objective: Seventy percent of patients with colorectal cancer (CRC) are aged 65 years or older. Netherlands Comprehensive Cancer Organization (n.d.) [1 ] Surgery is an important treatment modality, depending on cancer stage and the resectability of the tumor. Frail older patients are at an increased risk for complications and reduced self-care capacity after surgery. Increasing physical fitness preoperatively (prehabilitation) might improve treatment outcomes, but challenges remain with regard to uptake, attrition, and non-compliance. The objectives of this study were to investigate the barriers, facilitators, and preferences for preoperative exercise programs in older patients scheduled for CRC surgery. Methods: This was a qualitative study, using in-depth interviews of fifteen patients aged 65 years and older and surgically treated for CRC, thirteen informal care givers (ICs) and nine health care providers (HCPs) with experience in prehabilitation. Data analysis was done through thematic coding analysis. Results: Limited time, not receiving or misunderstanding information, physical ailments, and emotional impact of the diagnosis are barriers to preoperative exercise. Not having physical complaints (Patients, ICs, HCPs), understandable information provided by a physician (Patients, ICs), and low cost programs (ICs, HCPs) facilitate exercise. Exercise should not be too intensive (Patients, ICs) and should be adjusted to personal preferences and be provided close to home (Patients, ICs, HCPs). Conclusions: To engage frail older adults with CRC in preoperative exercise programs information on exercise should improve. Exercise programs should be easily accessible and take personal preferences, needs and abilities into account.